Activity participation on executive functions and well- being of hearing impaired children - Ayşe Göktaş; Alev Üstündağ; Aslı Zeynep Şahin (BMC Public Health)
Abstract Introduction The aim of the study was to examine the relationship between activity levels and psychological well-being and executive functions of children with hearing impairment. Method The study was conducted in seven schools providing education to hearing-impaired children in the Ankara province of Turkey. This cross-sectional-analytical study. The main data collection tools of the study were personal information form, Stirling Emotional and Psychological Well-being Scale for Children, Canadian Occupational Performance Measure and Childhood Executive Function Inventory Parent/Teacher Form. The relationships between the variables were evaluated using the Spearman correlation analysis and Multiple Linear Regression analysis was applied. Results A total of 69 students attending primary and secondary schools participated in the study. Eighty students were invited to participate in the study, but 69 of them agreed to participate in the study. The ages of the participants ranged between 4 and 12 years (mean: 12.48 ± 3.43 years). There was a statistically significant positive correlation between psychological well-being scale and activity performance (r = 0.275, p = 0.022). The contribution of age and activity performance variables to the model showing the effect of the Well-being Scale on the total score was statistically significant. The age and activity performance, which were the independent variables in the model, explained 29.9% of the changes in the Well-being Scale score. A one-unit increase of age caused a 0.976 standard deviation decrease in the Well-being scale score and a one-unit increase of the activity performance variable caused a 2.270 standard deviation increase in the Well-being Scale score. Conclusion The psychological well-being and executive functions were positively affected in hearing impaired children, and activity-oriented programs will make an important contribution to support psychosocial health and executive functions in managing this process.